Entrepreneurship through Innovation and Incubation in Agricultural Universities - Deka, Bidyut C (Indian Horticulture, 2024)
Empowering faculty to pursue entrepreneurship through innovation and incubation at Agricultural/ Horticultural Universities, by working on ideas that impact markets and communities, holds the key to transform our agricultural landscape and secure a sustainable future. By creating a robust ecosystem that nurtures agripreneurs, encourages innovation, and supports startups, we can unlock the true potential of our agriculture sector in Northeast India. Together, let us embark on this journey to empower the next generation of agripreneurs who will lead us towards a greener, more prosperous, and resilient world.